Electronic prescribing system design priorities for antimicrobial stewardship: a cross-sectional survey of 142 UK infection specialists. (19th December 2016) - Hand, Kieran S.; Cumming, Debbie; Hopkins, Susan; Ewings, Sean; Fox, Andy; Theminimulle, Sandya; Porter, Robert J.; Parker, Natalie; Munns, Joanne; Sheikh, Adel; Keyser, Taryn; Puleston, Richard
Abstract : Background: The implementation of electronic prescribing and medication administration (EPMA) systems is a priority for hospitals and a potential component of antimicrobial stewardship (AMS). Objectives: To identify software features within EPMA systems that could potentially facilitate AMS and to survey practising UK infection specialist healthcare professionals in order to assign priority to these software features. Methods: A questionnaire was developed using nominal group technique and transmitted via email links through professional networks. The questionnaire collected demographic data, information on priority areas and anticipated impact of EPMA. Responses from different respondent groups were compared using the Mann–Whitney U -test. Results: Responses were received from 164 individuals (142 analysable). Respondents were predominantly specialist infection pharmacists (48%) or medical microbiologists (37%). Of the pharmacists, 59% had experience of EPMA in their hospitals compared with 35% of microbiologists. Pharmacists assigned higher priority to indication prompt ( P  <   0.001), allergy checker ( P  =   0.003), treatment protocols ( P  =   0.003), drug–indication mismatch alerts ( P  =   0.031) and prolonged course alerts ( P  =   0.041) and lower priority to a dose checker for adults ( P  =   0.02) and an interaction checker ( P  <   0.05) than microbiologists. A 'soft stop' functionality was rated essential or high priority by 89% of respondents. Potential EPMA software features were expected to have the greatest impact on stewardship, treatment efficacy and patient safety outcomes with lowest impact on Clostridium difficile infection, antimicrobial resistance and drug expenditure. Conclusions: The survey demonstrates key differences in health professionals' opinions of potential healthcare benefits of EPMA, but a consensus of anticipated positive impact on patient safety and AMS.